Motivators influencing the efficiency and commitment of employees of agile teams - Mateusz Trzeciak; Paulina Banasik (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The production of new IT products and services in today's dynamic world of business and ever-evolving technology requires specific enterprise policies geared toward supporting innovation. Striving to provide the customer with the required value that meets the customer's current requirements is becoming quite a challenge for IT enterprises at this time. Moreover, innovative ideas are not created in "rigid" authoritarian-managed teams, but in an open culture based on the principles of self-organization and self-discipline, a characteristic of agile teams. One of the key determinants of a company's competitive advantage is employee effectiveness and commitment. Moreover, there are few publications covering research on employee effectiveness in agile teams. Therefore, the overarching goal of this article is to identify the motivators influencing the commitment and effectiveness of agile teams. In order to achieve the desired goal, an analysis of the research on the effectiveness and commitment of employees of a selected Polish IT company within the industry was conducted. As a result of the analysis of the obtained research results, seven determinants were developed, which have the greatest importance for agile teams and their motivation and effectiveness. Moreover, as the concluded research results show, the use of agile team models and open innovation positively affects the efficiency and commitment of employees.
Keywords: 650; agile; effectiveness; engagement; innovation; project management; project team